Tillage Intensity in a Long-Term Wheat-Sorghum-Fallow Rotation - A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2017)
This study was initiated in 1991 at the Kansas State University Southwest Research- Extension Center near Tribune, KS. The purpose of the study was to identify the effects of tillage intensity on precipitation capture, soil water storage, and grain yield in a wheat-sorghum-fallow rotation. Grain yields of wheat and grain sorghum increased with decreased tillage intensity in a wheat-sorghum-fallow (WSF) rotation. In 2016, available soil water at wheat and sorghum planting was greater for reduced tillage (RT) than no-tillage (NT) and least for conventional tillage (CT). Averaged across the 16-yr study, available soil water at wheat and sorghum planting was similar for RT and NT and about 1 inch greater than CT. Averaged across the past 16 years, NT wheat yields were 4 bu/a greater than RT and 7 bu/a greater than CT. Grain sorghum yields in 2016 were 15 bu/a greater with long-term NT than short-term NT. Averaged across the past 16 years, sorghum yields with long-term NT have been 70% greater than with short-term NT (68 vs. 40 bu/a).
Keywords: no-till; conventional tillage; reduced tillage; wheat-sorghum-fallow rotation; wheat; grain sorghum